Analysis of risk factors for recurrent stroke in stroke patients: Analisis Faktor Risiko Kejadian Stroke Berulang Pada Pasien Stroke - Luvty S.L. Dwiyanti; Syamsudin Abdillah; Ros Sumarny; M. Ivan Diandy (Universitas Muhammadiyah Purwokerto, 2026)
Stroke is the second leading cause of death after heart disease. It is reported that annually, over 15 million people worldwide suffer a stroke, resulting in disability or death. Indonesia has the highest stroke mortality rate among countries in Southeast Asia. Within 30 days, the risk of recurrent stroke is very high, with one contributing factor being non-adherence to antiplatelet therapy for recurrent stroke prevention. This study aimed to analyze medication adherence and risk factors associated with recurrent stroke incidents. The research employed an observational analytic method with a case-control study design. The study sample consisted of recurrent stroke patients and post-stroke patients, with 65 patients in each group, recruited from the neurology polyclinic of